Gagne and Laurillard's Models of Instruction Applied to Distance Education: A theoretically driven evaluation of an online curriculum in public health - Hannon, Peggy A.; Umble, Karl E.; Alexander, Lorraine; Francisco, Don; Steckler, Allan; Tudor, Gail; Upshaw, Vaughn (International Review of Research in Open and Distributed Learning, 2002)
This article presents an overview of the instructional models of Gagne, Briggs, and Wager (1992) and Laurillard (1993, 2002), followed by student evaluations from the first year of an online public health core curriculum. Both online courses and their evaluations were developed in accordance with the two models of instruction. The evaluations by students indicated that they perceived they had achieved the course objectives and were generally satisfied with the experience of taking the courses online. However, some students were dissatisfied with the feedback and learning guidance they received; these students’ comments supported Laurillard’s model of instruction. Discussion captured in this paper focuses on successes of the first year of the online curriculum, suggestions for solving problem areas, and the importance of the perceived relationship between teacher and student in the distance education environment.